2019
DOI: 10.1101/581892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing quality of reporting between preprints and peer-reviewed articles in the biomedical literature

Abstract: Preprint usage is growing rapidly in the life sciences; however, questions remain on the relative quality of preprints when compared to published articles. An objective dimension of quality that is readily measurable is completeness of reporting, as transparency can improve the reader's ability to independently interpret data and reproduce findings. In this observational study, we initially compared independent samples of articles published in bioRxiv and in PubMed-indexed journals in 2016 using a quality of r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…2) suggesting that, generally, preprints were relatively of good quality. Furthermore, recent studies have suggested that the quality of reporting in preprints differs little from their later peer-reviewed articles [44] and we ourselves are currently undertaking a more detailed analysis (see version 1 of our preprint for an initial analysis of published COVID preprints [45]). However, the problem of poor-quality science is not unique to preprints and ultimately, a multi-pronged approach is required to solve some of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…2) suggesting that, generally, preprints were relatively of good quality. Furthermore, recent studies have suggested that the quality of reporting in preprints differs little from their later peer-reviewed articles [44] and we ourselves are currently undertaking a more detailed analysis (see version 1 of our preprint for an initial analysis of published COVID preprints [45]). However, the problem of poor-quality science is not unique to preprints and ultimately, a multi-pronged approach is required to solve some of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that preprints are the solution to all issues around peer review and scholarly publishing, especially as they are still regarded in different ways by different communities; something that undoubtedly requires further study [99]. With the recent explosion of preprints in the Life Sciences [103], a number of different services have emerged that 'overlay' peer review in one form or another on top of the developing preprint infrastructure [104], for example, biOverlay in the Life Sciences. However, the general uptake of such services appears to be fairly low [105]; most recently, this led to Academic Karma, a leading platform in this area, to shut-down (April 2019).…”
Section: Beyond Traditional Peer Reviewmentioning
confidence: 99%
“…Empirical evidence to support the use of editors and peer reviewers as a mechanism to ensure the quality of biomedical research is relatively weak [21, 22] although other studies have rendered peer review as being potentially useful [23, 24]. This review provides some justification that preprint platforms might be a reasonable option for researchers, especially given the time spent and associated cost of peer review [25].…”
Section: Discussionmentioning
confidence: 99%